2022
DOI: 10.3390/healthcare10101921
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Older Patients′ Family Involvement by Nursing Staff in Hospitals: The View of Hospital Nurses in Israel

Abstract: According to the family-centered approach, the involvement of family in the care of hospitalized older patients is a crucial element of quality care. Active involvement of family in care by the nursing staff depends on different factors, including attitudes towards the importance of family in the care and perception of the interactions with the family. This study aims to identify the factors predicting staff behavior of involving the family in the care process. A cross-sectional study was conducted among 179 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…A hierarchical multiple linear regression was used to test the way specific individual and organizational factors affect nurses’ collaborative behavior. Following the first study in this series [ 29 ] (p. 9), the socio-demographic variables entered into the regression in step 1 were age, gender (as a dummy variable), years in the profession and education. Among the socio-demographic variables that were entered in the first step, it was found that only the two education variables were significant predictors of nurses’ collaborative behavior.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A hierarchical multiple linear regression was used to test the way specific individual and organizational factors affect nurses’ collaborative behavior. Following the first study in this series [ 29 ] (p. 9), the socio-demographic variables entered into the regression in step 1 were age, gender (as a dummy variable), years in the profession and education. Among the socio-demographic variables that were entered in the first step, it was found that only the two education variables were significant predictors of nurses’ collaborative behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Following the first article in this series [ 29 ] (p. 9), in step 1, education was a significant predictor of nurses’ collaborative behavior ( β = 0.31, p < 0.01 for bachelor’s degree and master’s degree). Further, in step 2, Fam-CP ( β = 0.26, p < 0.01), Fam-B ( β = −0.16, p < 0.05), Fam-OR ( β = 0.33, p < 0.001) and service climate ( β = 0.15, p < 0.05) were significant predictors of nurses’ collaborative behavior.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations